Svarājya-śishṭāī - Gandhi, Mahatma, 1869-1948 (Sulabha rāshṭrīya granthamālā ;, 1931)
Lectures and interviews at the time of Indian Round Table Conference, London, Sept. 7-Dec. 1, 1931, chiefly on the freedom movement in India.